Tác động lan tỏa của tăng trưởng kinh tế và trình độ dân trí đến độ che phủ rừng ở Việt Nam - Nguyen Huynh Mai, Tram; Nguyen Minh, Ha; Bui Hoang, Ngoc; Nguyen Van, Hieu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
In the age of globalization, efforts to protect environmental challenges from one individual, organizational, or local initiatives will not address all the issues. This highlights the critical need for collaboration between researchers and managers to harmonize their efforts towards common goals. This study aims to assess the direct and indirect impacts of economic growth and educational attainment on sustainable environmental practices (measuring by forest area coverage) in 60 provinces in Vietnam from 2013 to 2022. Furthermore, it examines the moderating role of digital transformation in the relationship between economic growth and forest coverage rate. In addition to providing empirical insights, this research offers strategic policy recommendations designed to empower environmental management agencies, fostering enhanced collaboration among provinces to protect Vietnam’s natural forests.